2010
DOI: 10.1364/oe.18.003477
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-terahertz reflectometry for health monitoring of ceramic thermal barrier coatings

Abstract: Terahertz time-domain reflectometry was used to monitor the progress of a thermally grown oxide layer and stress-induced, air-filled voids at the interface of an Yttria-stabilized-zirconia ceramic thermal-barrier coating and a metal surface. The thicknesses of these internal layers, observed in scanning-electron-microscope images to increase with thermal-exposure time, have been resolved - even when changing on the order of only a few micrometers - by distinguishing not only increased delays in the arrival tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…(7) to (10) into Eq. (6), we obtain Equation (11) shows that Γ < 0, so that Γ = -|Γ|. Rearranging Eq.…”
mentioning
confidence: 95%
“…(7) to (10) into Eq. (6), we obtain Equation (11) shows that Γ < 0, so that Γ = -|Γ|. Rearranging Eq.…”
mentioning
confidence: 95%
“…White et al [11] applied THz-TDS to the non-destructive evaluation (NDE) of yttria-stabilised zirconia (YSZ) coatings by imaging the thickness distribution and suggested that THz-TDS may potentially be used for the NDE of TBCs. Chen et al [12] investigated the dependence of the reflected THz time-domain waveform on the TGO thickness at the interface with an eye for using the TGO thickness to predict the remaining coating lifetime. However, they did not account for microstructure evolution, such as sintering and void growth, in the ceramic top layer during heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…There are other promising applications where THz has been tested even if less frequently. There is an increasing interest regarding THz application to detect and measure corrosion under paint for industrial applications [93][94][95][96]. This research could develop new THz methods for conservation of painted metal historical objects, such as furniture and sculptures.…”
Section: Other Applicationsmentioning
confidence: 99%